HISTORY OF THE MUGHAL DYNASTY: THE FUSION OF ISLAMIC AND HINDU CULTURE IN INDIA - Aisyah Zahratunnisa; Danang Syaifulloh; Fajar Fajar; Ahmad Maftuh Sujana (Jurnal Intelek Insan Cendikia, 2025)
The Mughal Dynasty was one of the largest empires in Indian history, lasting from the 16th to the 19th century. It was founded by Babur in 1526 after his victory at the Battle of Panipat. During its golden age, the Mughal Dynasty was not only known for its territorial expansion and strong administration but also for its success in uniting elements of Islamic and Hindu culture in India. Through tolerance policies introduced by emperors like Akbar, the Mughals created social harmony that allowed the flourishing of art, architecture, and an inclusive governance system. This cultural fusion was reflected in various aspects of life, including the architecture of the Taj Mahal and the Red Fort, as well as in the legal and administrative systems that accommodated diverse social groups. However, the weakening of leadership and increasing pressure from colonial forces led to the fall of the dynasty in the 19th century. This article explores the history of the Mughal Dynasty, focusing on its role in shaping a cultural synthesis that had a lasting impact on Indian history.